Analisis Etika Periklanan Politik Era Soekarno (1945-1967) - Yusuf, Mohamad Faiq Rizkiansyah; Kamil, Muhamad Gibraltar; Handoko, Daniel (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
Press Ethics are principles and guidelines for regulating the behavior and practices of journalism activities. The main function of ethics is to ensure that the news and information presented are carried out fairly, accurately, and responsibly. This makes press ethics important to maintain and implement to maintain the integrity, trust, and credibility of the press. However, these ethics always change from time to time, following the current political, economic, social, and cultural developments in a country. In this research, we will reveal the role and ethics of the press during the political era of the Soekarno era 1945-1967). It was found that based on authoritarian press theory, press ethics at that time were heavily influenced and controlled by the government, and emphasized the implementation of NASAKOM ideology by members of the press. Therefore, this research reveals several press guidelines, the conditions of the press, and the implementation of these ethics in society during the Soekarno political era. Keywords: Authoritarian Press Theory, Nasakom Ideology, Soekarno of  Era Press Ethics